Food safety in developing countries: An overview - Grace, Delia (CAB International, 2015)
This resource has been put together to help livelihoods advisers and other interested development professionals critically think through the issues concerning food safety in developing countries. The aim is to engage readers unfamiliar with the subject and to refresh and update knowledge on food safety for others. It is hoped that the material will provide ‘non-food safety experts’ with a good understanding of foodborne disease within the broader context of ‘development’ discussions. It is assumed that readers already have a solid grasp of international development contexts, and current development discourse. Foodborne diseases (FBD) can be defined as any illness caused by ingesting contaminated food or drink. The most common clinical presentation of foodborne diseases is gastrointestinal symptoms, but foodborne diseases can also lead to chronic, life-threatening symptoms including neurological, gynaecological or immunological disorders as well as multi-organ failure, cancer and death. The material presented in this resource reviews foodborne disease in developing countries. It covers the following: the likely burden of foodborne disease; the importance of foodborne disease to developing countries; the causes of foodborne disease and the most risky foods; trends in foodborne disease; and the management of foodborne disease. It is presented in 3 main sections: Part 1 will help readers to understand what is meant by foodborne disease and its impact. It summarises current best evidence and knowledge gaps on foodborne disease in developing countries. Part 2 summarises some of the interventions for managing food safety and stimulates thinking about the “so what” questions. It shows that foodborne disease is preventable. Part 3 covers food trends and drivers that affect food safety in developing countries in more detail. It also reviews the geography of food safety and how this impacts on people who are poor, and looks at what food safety means for: small farmers, export industries, women, the most vulnerable people, and for nutrition. The conclusions presented at the end capture what the current best evidence is telling us: Food safety has been neglected in developing countries. There is growing evidence that foodborne disease may be an important contributor to gastrointestinal disease. Foodborne disease has been increasing in developed countries and is likely to increase in developing countries. Foodborne disease is not just a health issue. Already a major determinant of export market access, it is increasingly affecting domestic markets. This peer reviewed learning resource has been produced by the International Livestock Research Institute in partnership with Evidence on Demand and with the assistance of the UK Department for International Development (DFID) contracted through the Climate, Environment, Infrastructure and Livelihoods Professional Evidence and Applied Knowledge Services (CEIL PEAKS) programme, jointly managed by DAI (incorporating HTSPE Limited) and IMC Worldwide Limited.